Determinan Aspek Rasio Ketergantungan Masa Covid-19 Dan Sebelum Masa Covid-19 Di Indonesia - Pratama, Andik; Ningsih, Endah Ayu N. L. (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
In this study, the analysis was carried out before and during the COVID-19 pandemic with the aim of research to find the direction of relationships and influences between variables. The variables chosen to test the factors affecting the dependency ratio are Open Unemployment Rate, Economic Growth, Poverty, Inflation and Number of Working People. The analysis used the Vector Autorgression (VAR) model and the results contained two variables that affect the dependency ratio, namely the open unemployment rate and poverty.